Novel Bioactive Hybrid Composites Based on Coordination Compounds of Some Tertiary Arsines with Mercury(II) Halides - Rusia, M.; Lekishvili, N.; Barbakadze, Kh.; Gverdtsiteli, M.; Lekishvili, Giorgi (Asian Journal of Chemistry, 2012)
The novel arsenic-containing coordination compounds with the bridge structure were synthesized and studied. Antibiocorrosion covers based on synthesized compounds have created. Some of the mechanical and exploatative characteristics have been determined.